Multi-accelerant approach for rapid shelf-life determination of beverages in polymeric packaging - Muniandy A. (2023)
An effective analysis method with multiple accelerant factors is needed for shelf-life determination and prediction for food products with reduced analysis time. Raising the storage temperature is the most common approach utilized in the conventional accelerated shelf-life test (ASLT) to reduce the shelf-life testing time of food. Oxygen pressure as an accelerant for the shelf-life determination of food products has not been given much attention even though it has shown a negative impact on food shelf-life. Combining oxygen pressure and temperature as accelerants has the potential to further reduce the overall analysis time compared to the ASLT. This study focuses on the effects of applying oxygen pressure and temperature as multi-accelerants on the shelf-life of a shelf-stable product by investigating the extent of vitamins degradation and modeling the reaction using a mechanistic approach. A shelf-stable model food fortified with vitamins A, B1, C and D3 was developed to investigate the effect of multiple accelerants on the quality indicators of shelf-stable foods in a polyethylene terephthalate (PET) container. PET bottles filled with model food were placed in a high-pressure (138 kPa) 100% oxygen environment at 40 °C. This novel process is named as the ultra-accelerated shelf-life test (UASLT). Samples were also subjected to ASLT conditions at 40 °C and control condition at 22.5 °C, both at ambient pressure for comparison. UASLT treatment induced a rapid degradation of 27.1 ± 1.9%, 35.8 ± 1.0%, and 35.4 ± 0.7% in vitamins A, C and D3, respectively, in just 50 days. Slower degradation was observed with samples kept under the ASLT conditions for 105 days with a degradation of 24.0 ± 2.0%, 32.0 ± 3.1% and 25.1 ± 1.5% for vitamin A, C and D3, respectively. The control samples that were studied for 210 days showed 14.9 ± 5.0%, 13.8 ± 2.2% and 10.6 ± 0.8% degradation in vitamins A, C and D3, respectively. The increase in the ΔE values due to browning in samples kept at the UASLT, ASLT and control conditions were 11.67 ± 0.09, 7.49 ± 0.19 and 2.51 ± 0.11, respectively. The degradation of vitamin B1 was similar across the treatments. The addition of oxygen pressure significantly increased the degradation reaction rates of the vitamins and color due to the rapid influx of oxygen. A mechanistic model that coupled oxygen diffusion and simultaneous vitamin degradation provided a good fit to the experimental data for the UASLT treatment with a rate constant of 0.686, 0.631 and 0.422 M−1day−1 for vitamins C, D3 and A, respectively. Elevated external oxygen pressure can be used as an accelerant along with moderate temperatures for rapid shelf-life testing of products in polymeric packaging with two-fold reduction in the overall analysis time as compared to ASLT.